2015
DOI: 10.9738/intsurg-d-14-00183.1
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Inferior Right Hepatic Vein–Conserving Segments 7 to 8 Resection of the Liver

Abstract: This study aims to investigate the safety of inferior right hepatic vein (IRHV)-conserving surgery by comparing the surgical data and postoperative complications between IRHVconserving segments 7 to 8 (S7 to S8) resection and conventional right hemihepatectomy (RH). Five patients who underwent IRHV-conserving S7 to S8 segmentectomy between 2007 and 2011 (IRHV group) and 25 liver cancer patients who underwent RH without biliary tract reconstruction during the same period (RH group) were investigated. The surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
1
0
2
Order By: Relevance
“…Накоплен и опыт резекций верхних сегментов печени с печеночными венами, преимущественно ППВ без ее последующей реконструкции, в том числе при отсутствии нижней ППВ, что не сопровождалось нарушением венозного оттока от сохраняемых нижних сегментов [15,16]. [17].…”
Section: Discussionunclassified
“…Накоплен и опыт резекций верхних сегментов печени с печеночными венами, преимущественно ППВ без ее последующей реконструкции, в том числе при отсутствии нижней ППВ, что не сопровождалось нарушением венозного оттока от сохраняемых нижних сегментов [15,16]. [17].…”
Section: Discussionunclassified
“…There were several reports on a technique to determine the liver transection line in IRHV-preserving hepatectomy. Nakayama et al decided the transection line based on the discolored congested area made by cramping the RHV and right hepatic artery [ 31 ]. Sugimachi et al also demonstrated the modified hanging maneuver with taping of the IRHV to determine the transection line between segment 6 and 7 [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…В представленной работе показана возможность решения такой задачи, которая периодически появляется при локализации новообразования в VII-VIII сегментах печени в непосредственной близости от ствола правой печеночной вены (ППВ) и (или) формирующих его ветвей. Обычно в подобной ситуации объем операции вынужденно расширяют до правосторонней гемигепатэктомии, реже выполняют резекцию печени и участка ствола вены с последующей реконструкцией для обеспечения адекватного венозного оттока от VI и латеральной части V сегмента [5][6][7]. Также в литературе описана возможность перевязки ППВ без реконструкции, но только при наличии короткой печеноч-ной вены диаметром >5 мм -так называемой нижней ППВ (НППВ) [8][9][10][11].…”
Section: вве де ниеunclassified